Socio-Cultural Transformation of Saudi Arabia Under the Leadership of Muhammad Bin Salman - Nadia Azahra Hidayat; Yon Machmudi; Izdiyan Muttaqin (International Journal of Islamic Business and Management Review, 2025)
Purpose – This study aims to examine the purposes and implications of socio-political changes and cultural dynamics in Saudi Arabia under the de facto leadership of Mohammed bin Salman (MBS), particularly through the Vision 2030 reform agenda. The study explores how Vision 2030 reflects the tensions between modernization efforts and enduring political-cultural conservatism within Saudi society. Methodology – Using a qualitative exploratory approach and a descriptive-analytical strategy, the research draws on foreign policy theories by James N. Rosenau and Marijke Breuning to analyze how domestic reform is shaped by both internal dynamics and global pressures. Data were collected through a literature review of credible secondary sources, including official documents, public statements, and academic publications, and analyzed thematically through coding and contextual interpretation. Findings – The study finds that while Vision 2030 promotes social liberalization and national identity reconstruction, the reform process remains tightly governed by political authority and religious conservatism, revealing a sustained tension between progressive change and authoritarian continuity. Conclusion – These developments suggest that the reforms under MBS represent not a democratic transition, but a calculated modernization project that preserves state control while signaling change. Contribution/Novelty – This paper offers a critical perspective on Saudi Arabia's reform era, arguing that Vision 2030 operates as an ideological and hegemonic project, and provides insights into how culture becomes a contested space in authoritarian modernization processes.